Utilization of E-Voting as A Medium for Decisions Making on The Use of Village Funds - M. Khairul Anam; Mega Susanti; Susanti Susanti; Nurjayadi Nurjayadi; Helda Yeni (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2022)
Each region in Indonesia has advantages and disadvantages, such as location, facilities, and infrastructure. These advantages and disadvantages give rise to social inequalities, especially in rural areas. To minimize social inequality, the government provides village funds that can be used to build facilities and infrastructure, training, and tourism development through Village-Owned Enterprises (BUMDes). The use of village fund assistance is discussed in village council meetings with the community. Some of the obstacles faced in the deliberations are the minimal attendance of participants, less than optimal participants getting information and giving opinions, and the corona virus-19 pandemic. Public concern about the COVID-19 pandemic has turned face-to-face meetings into virtual ones. In this study, public opinion obtained from village e-voting is processed using TF-IDF which aims to give weight to words as a reference in determining development priorities and empowerment needed by the community. After the system is completed, the system is tested with three characteristics of ISO 9126: usability, efficiency, and functional test. The results obtained from testing ISO 9126 are 86.5% for usability, 80% for efficiency, and 75.5% for functionality. TF-IDF generates requests for empowerment, improved facilities and infrastructure, and education. In the word cloud, empowerment becomes the most dominant, depicting it as the biggest. The results showed that the community's priorities and the results of the system were running well.